Pride and Prejudice: The Human Side of Incentive Theory - Ellingsen, Tore; Johannesson, Magnus (American Economic Review, 2008)
Desire for social esteem is a source of prosocial behavior. We develop a model in which actors' utility of esteem depends on the audience. In a principal-agent setting, we show that the model can account for motivational crowding out. Control systems and pecuniary incentives erode morale by signaling to the agent that the principal is not worth impressing. The model also offers an explanation for why agents are motivated by unconditionally high pay and by mission-oriented principals. (JEL D01, D82)